The study aims to determine the effect of Intellectual Capital, Capital Structure and Institutional Ownership on Financial Performance with Company Size as Moderating in financial sector companies listed on the Indonesia Stock Exchange (BEI) Period 2020-2 - Kusniawati, Heni; Nuryatno Amin, Muhammad (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Pengaruh Intellectual Capital, Struktur Modal, Kepemilikan Institusional Terhadap Kinerja Keuangan Dengan Ukuran Perusahaan Sebagai Pemoderasi